2020
DOI: 10.3390/app10103376
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Frequency Support from a DFIG-Based Wind Turbine Generator via Virtual Inertia Control

Abstract: As the penetrated level of wind in power grids increases, the online system inertia becomes weak. Doubly-fed induction generator (DFIG)-based wind turbine generators (WTGs) are required to provide virtual inertia response to support system frequency. The present inertia control strategy with fixed control gain is not suitable and may cause stall of the DFIG-based WTG, as the virtual inertia response potential from the DFIG-based WTG is different with various wind speed conditions. This paper addresses a virtua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The suggested technique considers multiple frequency coefficients to maintain the frequency level under varied load scenarios. Reference [120] proposes another VIC approach for DFIG-based WTs to provide frequency stability in the microgrid. The results of simulations for various operating circumstances offer a more reliable approach than other approaches.…”
Section: Figure 9 (Continued)mentioning
confidence: 99%
“…The suggested technique considers multiple frequency coefficients to maintain the frequency level under varied load scenarios. Reference [120] proposes another VIC approach for DFIG-based WTs to provide frequency stability in the microgrid. The results of simulations for various operating circumstances offer a more reliable approach than other approaches.…”
Section: Figure 9 (Continued)mentioning
confidence: 99%
“…Wind power plants in operation have a certain amount of kinetic energy available in the rotating blade, gear and generator, allowing the short-term power output to increase by reducing the rotational speed of the turbine. It has been shown that wind power plants are capable of delivering this kind of active power service [37][38][39].…”
Section: Vsm Control In the Wind Power Plantsmentioning
confidence: 99%
“…For a long time, researchers have conducted a series of studies on reducing the frequency nadir (FN) and the rate of change of frequency (ROCOF) of the power system based on the introduction of inertial control (Mandal and Chatterjee, 2021) (Xu et al, 2019). In order to get rid of the inherent adverse effects of the inertial control strategy with constant parameters, Hwang et al (2016), Pradhan et al (2018), Wu et al (2018), and Yang et al (2020) proposed an inertial control method based on dynamic gain to improve the frequency stability of the system under fixed wind conditions. Sato et al (2022) designed a novel virtual inertia control strategy based on fuzzy logic controller (FLC) to reduce the FN.…”
Section: Introductionmentioning
confidence: 99%